A study of social media’s effectiveness influencing consumer behavior in China: Generation Y’s purchasing behavior on cosmetic goods - Cui, Yuanshu (2014)
Social media is playing important to affect consumer behavior. People can share their knowledge, opinions, and experiences with one other due to the social media provided features, and it may impact on people’s behavior in terms of communication and purchasing.